LEGISLASI HUKUM KELUARGA ISLAM BERDASARKAN KOMPILASI HUKUM ISLAM - Keri, Ismail (Institut Agama Islam Negeri (IAIN) Bone, 2017)
Islamic Family Law consists of fundamental nationalities that always live and develop along with the development of society in the life of the nation. The configuration of national life interests is an instrument contested by the nation's components in these interests in the path of the state constitution, thus gaining a place of legitimacy in the process of constructing a national legal order. The history of national legal legislation has included the Compilation of Islamic Law as one of the country's alignments with the process of Islamic family law into National law. At the same time, the recovery of the development of Islamic Family Law is increasingly lively as the process of finding answers to Islamic problems in the archipelago's insight, how: Compilation of Islamic Law accommodates changes in the application of Islamic family law in Indonesia?The description that can be obtained in this study shows that based on the history of beginning, the Compilation of Islamic Law is present as meeting the needs of the Islamic community as well as filling in the gaps that occur in the Religious Courts whose authority is regulated in Law No. 7 of 1989. However, in its journey, a number of studies and studies explained that the Compilation of Islamic Law contained a variety of potential criticisms, in which the Compilation of Islamic Law was deemed to be no longer sufficient in resolving various complex complexity problems. Therefore it is necessary to reconstruct the Compilation of Islamic Law by paying attention to the principles of equality (al-muswah), brotherhood (al-ikhâ`), and justice (al-`adl), as well as basic ideas for the formation of civil society, such as pluralism, gender equality , Human rights, democracy, and egalitarianism, so that the needs of Islamic family law can be fulfilled in several such as Constitutional aspects, Content aspects (Material / Content and Ideas), Aspects of Islamic Law Enforcement (rule of law) in the Indonesianness frame.